Building Environmental Awareness among Preschoolers through Simple Hydroponic Farming: A Community Service at ABA XVI Kindergarten North Purwokerto, Banyumas Regency - Syarifah, Risqa Naila Khusna; Shofa, Eros Meilina; Bayyinah, Lafi Na'imatul; Novitasari, Dian; Purwanto, Purwanto; Sarjito, Agus; Hanifa, Hana; Ratnaningsih, Hanim Rahayuani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The decreasing interest of the younger generation in agricultural activities poses a serious challenge for future sustainability. Integrating environmental education into early childhood learning is therefore essential. This community service activity aimed to introduce eco-friendly farming practices to preschoolers at TK ABA XVI, North Purwokerto, Banyumas Regency through a simple hydroponic system using recycled waste materials. The program involved interactive lectures, discussions, Q&A sessions, and hands-on hydroponic planting. Results showed an increase in students' knowledge about hydroponics and a growing awareness of the importance of recycling plastic waste to protect the environment. This initiative highlights the effectiveness of early intervention in cultivating environmental consciousness among young learners.